The Development of Supplement Book on Biodiversity Chapter Based on Dragonfly Diversity in Lusi Watershed - Peryana, Riska; Anggraito, Yustinus Ulung; Widiatningrum, Talitha (FMIPA UNNES, 2021)
The Lusi River has local potential for abundant biodiversity, one of them is the diversity of dragonfly species. This local potential can be compiled into a teaching supplement to complement the student's teaching book. Data on the diversity of dragonflies in the Lusi watershed of Blora region was successfully obtained and compiled as a supplementary book of biodiversity chapters. However, the feasibility of the book needs to be assessed by material experts, media experts, teachers, and students. The purpose of this study was to analyze the feasibility and response of teachers and students to the supplement book developed. This study is designed as Research and Development (R&D) that is limited to the small-scale test stage. Eligibility data obtained by using media validation questionnaires and questionnaires made in accordance with BSNP 2014 standards, while teacher and student response data is obtained by using teacher and student response questionnaires. The validation of material experts against teaching supplements got a score of 93.23% and media experts gave a score of 98.61%, both with very decent categories. However there are suggestions from material and media validators for minor revisions. Teacher and student responses to teaching supplement received scores of 91.83% and 97.3% respectively with very decent categories. Based on the results of the study, it can be concluded that the teaching supplement of dragonfly diversity in Lusi River watershed is feasible for use in the study of biodiversity chapters.